VPg Impact on Ryegrass Mottle Virus Serine-like 3C Protease Proteolysis and Structure - Kalnins, Gints; Ludviga, Rebeka; Kalnciema, Ieva; Resevica, Gunta; Zeltina, Vilija; Bogans, Janis; Tars, Kaspars; Zeltins, Andris; Balke, Ina (International journal of molecular sciences, 2023)
Sobemoviruses encode serine-like 3C proteases (Pro) that participate in the processing and maturation of other virus-encoded proteins. Its cis and trans activity is mediated by the naturally unfolded virus-genome-linked protein (VPg). Nuclear magnetic resonance studies show a Pro–VPg complex interaction and VPg tertiary structure; however, information regarding structural changes of the Pro–VPg complex during interaction is lacking. Here, we solved a full Pro–VPg 3D structure of ryegrass mottle virus (RGMoV) that demonstrates the structural changes in three different conformations due to VPg interaction with Pro. We identified a unique site of VPg interaction with Pro that was not observed in other sobemoviruses, and observed different conformations of the Pro β2 barrel. This is the first report of a full plant Pro crystal structure with its VPg cofactor. We also confirmed the existence of an unusual previously unmapped cleavage site for sobemovirus Pro in the transmembrane domain: E/A. We demonstrated that RGMoV Pro in cis activity is not regulated by VPg and that in trans, VPg can also mediate Pro in free form. Additionally, we observed Ca2+ and Zn2+ inhibitory effects on the Pro cleavage activity.